Terengganensines A and B, dihydroeburnane alkaloids from Kopsia terengganensis - Uzir, S.; Mustapha, A.M.; Hadi, A.H.A.; Awang, Khalijah; Wiart, C.; Gallard, J.F.; Pais, M. (1997)
Five known indole alkaloids, (+)-quebrachamine. (-)-eburnamine, (+)-isoeburnamine, (-)-eburnaminol and (+)-larutensine, and two new alkaloids, terengganensines A 1 and B 2, possessing a unique dihydroeburnane skeleton were isolated from the bark of Kopsia terengganensis. The structures of the new compounds were elucidated by spectral methods. (C) 1997 Published by Elsevier Science Ltd.